2018
DOI: 10.1097/nne.0000000000000423
|View full text |Cite
|
Sign up to set email alerts
|

Process Matters

Abstract: Researchers who study nursing education encounter difficulty when trying to recruit and retain nurse educator participants. Researchers would benefit from knowing more about effective and ineffective sampling strategies and methods to increase the efficiency of the research process. This article outlines the struggles and successes encountered with a mixed methods study that examined nurse educators’ critical thinking. Specific examples are interwoven with current literature to uncover some important insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Involving practitioners who work in acute care settings in research efforts, qualitative or otherwise, is often a difficult and timeconsuming task. Increasing workplace demands driven by patient acuity, staffing, and other contextual factors have made participant recruitment increasingly difficult (Broyles et al, 2011;Hysong et al, 2013;Raymond, Profetto-McGrath, Myrick, & Strean, 2018). Researchers have reported that being present on the clinical unit and establishing a rapport with frontline staff contribute to successful recruitment of practitioners as participants (Flynn et al, 2018;Hysong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Involving practitioners who work in acute care settings in research efforts, qualitative or otherwise, is often a difficult and timeconsuming task. Increasing workplace demands driven by patient acuity, staffing, and other contextual factors have made participant recruitment increasingly difficult (Broyles et al, 2011;Hysong et al, 2013;Raymond, Profetto-McGrath, Myrick, & Strean, 2018). Researchers have reported that being present on the clinical unit and establishing a rapport with frontline staff contribute to successful recruitment of practitioners as participants (Flynn et al, 2018;Hysong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…White (2012) found that prospective nurse study participants had become “tired and disinterested” in participating in research as they had been frequently invited to participate in studies in the past two decades. Consequently, researchers run the risk of low participation and incomplete survey responses when recruiting nurses in the hospital setting (Raymond et al, 2018). Mulhall (1997) identified that researchers and leaders in the practice environment operate under different imperatives and foci, which remains true today (Huston et al, 2018).…”
mentioning
confidence: 99%
“…Pelo método, o pesquisador desenvolve e controla ativamente e deliberadamente o início, o progresso e o término da amostra. O método garante que esse início seja realizado de forma aleatória, pois é resultado de uma crescente sensibilidade do autor que está mergulhado no seu campo de pesquisa (Raymond et al, 2018) Para o primeiro recrutamento do possível participante, foi selecionado um enfermeiro da rede de contado da pesquisadora. Dessa forma, o primeiro contato foi realizado por meio de um aplicativo de mensagens de texto instantâneas.…”
Section: Recrutamento Dos Participantesunclassified